Suicidal ideation and coping styles in adolescents from educational institutions - Cárdenas Vila, Roxana Maribel (2018)
This research had as main objective establish the relationship between suicidal ideation, and coping styles in a sample of 353 adolescent students in educational institutions between 13 and 18 years old. We used the Suicidal Ideation Scale PANSI and Coping Scale for adolescents (ACS). Significant correlations between these variables were found. Regarding suicidal ideation students reported having 24% of ideation at a high level; level coping styles, non-productive style was the most used (37.7%). Significant differences regarding suicidal ideation and coping styles were found by sex.